Changes in Choroidal Thickness Varied by Age and Refraction in Children and Adolescents: A 1-Year Longitudinal Study - Xiong, Shuyu; He, Xiangui; Zhang, Bo; Deng, Junjie; Wang, Jingjing; Lv, Minzhi; Zhu, Jianfeng; Zou, Haidong; Xu, Xun (American journal of ophthalmology, 2020)
To clarify the changing characteristics of choroidal thickness over time within different age ranges and among different refractive statuses of children aged 6 to 18 years. Prospective cohort study. Data of axial length, cycloplegic refraction, and choroidal thickness (using swept-source optical coherence tomography) were collected at baseline and at a 1-year follow-up for 756 participants. One-year change in choroidal thickness and its association with age and refraction were analyzed. Significantly greater attenuation of choroidal thickness was observed in younger children aged 6-9 years for all participants (−9 ± 25 μm) and for those with a myopic shift (−12 ± 25 μm), whereas there was a larger increase in adolescents aged 10-13 years for those without a myopic shift (9 ± 23 μm). There was a marked decrease in the choroidal thickness for newly developed myopic patients compared with persistent-nonmyopic patients and persistent-myopic patients (P < .01). The association between changes in axial length and choroidal thickness was less strong in persistent-myopic patients (β = −15.4, P = .022) than that in persistent-nonmyopic patients (β = −30.4, P < .001) and newly developed myopic patients (β = −33.7, P = .001), whereas among the persistent-myopic patients, the association was less strong in the baseline mild-myopic patients (β = −10.4, P = .193) than that in the baseline moderate-to high-myopic patients (β = −31.4, P = .026). Changes in choroidal thickness varied by age. There was an increased rapid thinning of the choroid among newly developed myopic patients, and a nonsignificant association between changes in choroidal thickness and axial length in the early stages of myopia.